Bacterial community shifts in Fusarium-induced avocado root rot and the antagonistic potential of Bacillus siamensis NB92 - Wang, Chengxian; Song, Zhijiao; Li, Xue; Liu, Qing (Frontiers in Microbiology, 2025)
Avocado root rot, driven by soil-borne fungi such as Fusarium spp., poses a major challenge to global avocado production. The rhizosphere microbiome is critical for plant health, yet the impact of root rot on bacterial community structure and its implications for disease management remain poorly understood. Here, we combined culture-independent 16S rDNA amplicon sequencing with culture-dependent isolation to characterize bacterial communities in healthy and Fusarium-infested avocado bulk and rhizosphere soils. Key beneficial taxa, notably Bacillus, were then isolated and evaluated for their antagonistic potential. Results showed that root rot significantly reduced rhizosphere bacterial α-diversity, altered community structure, and depleted phyla such as Actinobacteriota and Firmicutes that contain beneficial taxa. Beneficial genera such as Bacillus and Streptomyces declined, while cultivable Fusarium counts increased. Negative correlations between Fusarium abundance, the bacteria-to-fungi ratio, and the relative abundance of beneficial bacteria further underscore their suppressive role. Guided by these findings, we isolated Bacillus strain NB92, identified as Bacillus siamensis through morphological, biochemical, and 16S rRNA and gyrA gene analyses. NB92 exhibited strong antagonistic activity against the root rot pathogen (Fusarium sp. St7) via both direct antagonism and volatile organic compound production. Inoculating NB92 into diseased rhizosphere soil boosted Bacillus counts and reduced Fusarium abundance. Moreover, NB92 effectively inhibited the pathogen’s necrotizing ability. B. siamensis NB92 thus represents a promising, sustainable biocontrol agent and contributes to the development of microbiome-based strategies for managing avocado root rot.